Investigation to Predict Primary Implant Stability Using Frictional Resistance Torque of Tap Drilling - Kaien Wakamatsu; Kazuya Doi; Reiko Kobatake; Yusuke Makihara; Yoshifumi Oki; Kazuhiro Tsuga (Stilus Optimus, 2022)
Objectives: The purpose of this experimental study was to investigate the correlation between the frictional resistance torque of tap drilling prior to implant placement and the primary stability after implant placement. Material and Methods: Solid rigid polyurethane bone blocks of four different densities were used in this study. A computerized surgical implant motor device was utilized to measure the frictional resistance torque of tap drilling. After the tap torque was measured, the dental implants were inserted at the prepared sites. During the implantation, the insertion torque was recorded, and resonance frequency analysis was performed, the value of which was calculated as the implant stability quotient. Thereafter, the correlation between the tap torque and the primary stability of the implant was evaluated and compared with the standard drilling protocol. Results: A significant positive correlation was found between the tap torque and insertion torque (Pearson's r = 0.88, P < 0.0001). Similarly, there was a positive correlation between the tap torque and implant stability quotient (Pearson's r = 0.69, P < 0.0001). Conclusions: These results suggest that measurement of the frictional resistance torque of tap drilling prior to implant placement could provide helpful information for implant primary stability.